Maṇi muḻaṅṅunnu - Nampyār, Uṣā (Sāhityapṟavarttaka Sahakaraṇasaṅghaṃ, 1999)
Short-stories based on social themes.
Malayalam in Malayalama-Schr
Keywords: Malayalam; Kurzgeschichte; Geschichte 1900-2000